Assessment of whole-body vibration and development of mitigation intervention for single-axle tractor–trailer combination - Naveen, Rachamalla; Kumar, Adarsh; Kumar, Rajeev; Kushwaha, H. L.; Khanna, Manoj; Ramasubramanian, V.; Poojith, Sajja (Frontiers in Mechanical Engineering, 2024)
IntroductionTractarization is synonymous with farm mechanization in India. Tractor-trailers are extensively used for the transportation of farm inputs and produce on and off-road, exposing drivers to excessive vibration.ObjectivesThe study was undertaken to assess tractor drivers’ vibration exposure while using trailers and to develop low-cost mitigation interventions.MethodologyThe whole-body vibrations were measured at the tractor seat during the transportation with a no, half (3715 kg soil) and full payload (5910 kg soil) trailer on two terrain conditions, namely, asphalt and farm terrains. The speeds recommended by ISO 5008-1979 of 10, 12 and 14 km/h on asphalt roads and 4, 5 and 7 km/h on farm roads, as well as actual working speeds preferred by the operator (18, 20 and 22 km/h on asphalt road and 8, 10 and 12 km/h on farm terrain), were selected for experiments. Two vibration reduction interventions, namely spring suspended single point hitch (I1) and polyurethane (PU) bush (I2), were developed and installed between the tractor and trailer. Whole-body vibration (WBV) was measured by repeating the experiments.ResultsThe maximum vibration reduction on asphalt road at 22 km/h with I1 was found as 14.3, 19.03 and 23.1%, whereas on-farm terrain at 12 km/h was found as 15.16, 22.43, and 25.56% for no, half and full payload. Similarly, with I1 + I2 interventions, the maximum total vibration reduction at 22 km/h was 16.86, 21.12 and 25.51% on asphalt roads, whereas on-farm tertian at 12 km/h was 17.07, 23.77 and 28.67%. The average value of lower health guidance caution zone (HGCZ) limits on asphalt roads increased by 1.11, 0.95 and 0.92 h and on-farm tertian 1.55, 1.14 and 0.83 h with no, half, and full payload. The average value of upper HGCZ limits on asphalt roads increased by 3.13, 3.21 and 3.68 h and on-farm tertian by 2.24, 2.94 and 3.31 h with intervention.ConclusionsThis infers that with developed interventions an operator can safely perform for a longer duration and at higher operational speeds because of the reduced vibration.